172 Racial Trends in Peyronie's Disease Treatments: Analysis of the Veterans Health Administration. Issue 1 (1st April 2022) - Nackeeran, S.; Masterson, T.
ABSTRACT: Introduction: Racial disparities are known to affect urologic care. Settings such as the Veterans Affairs (VA) health system, where access to care is more equitable, have noted reductions in racial disparities for certain diseases. Previous studies of Peyronie's Disease (PD) have investigated responses to treatment by race, but not treatment rates themselves. Frequently, racial disparities in healthcare are attributed to differences in income or decreased insurance rates among people of color. For this reason, we aimed to investigate racial disparities in PD treatments by evaluating the VA Informatics and Computing Infrastructure (VINCI), which contains data from the VA. As veterans are insured and able to obtain treatment for PD through the VHA, this population allows us to study the effects of race on treatment rates when insurance does not serve as a barrier. Objective: To evaluate the treatment rates for Peyronie's Disease within the VA by race in order to determine whether racial disparities exist when insurance access is equitable. Methods: We queried VINCI to obtain data for a cohort of men that have a recorded diagnosis of PD by ICD-9 or ICD-10 code between 2015-2020. We then used the following CPT codes to identify which patients had procedures known to be therapeutic for PD: plaque injection (CPT 54200), penile prosthesis (54400, 54405), penile reconstruction to correct penis angle (54360), or plaque excision (54110, 54111, 54112). We evaluated treatment rates among patients with race/ethnicity information recorded. We reported results as frequencies and used the chi-square test to evaluate significant differences in treatment rates when comparing racial groups to Whites, with statistical significance reported at p<.05. Results: We obtained data for 17, 022 patients with diagnoses of PD. Within the total population of patients diagnosed with PD, 71.4% were White (Non-Hispanic), 25.4% were Black, 5.8% were Hispanic or Latino, 0.3% were Asian or Pacific Islander (API), and 1.6% were Native American (NA), and 5.4% were unknown. Among this cohort, 13.6% of all patients, 13.6% of Whites, 14.3% of Blacks (p=0.2985), 13.5% of Hispanics (p=0.9205), 9.1% of API (p=0.3319), 16.7% of NA (p=0.1406), and 9.6% of unknown (p=0.0041) were treated. Conclusions: Within the VHA population, which is not limited by access to health insurance, all patients with recorded race information were treated at similar rates for PD to Whites. Only those without racial information recorded were treated at a significantly lower rate. This study demonstrates the potential for equitable insurance and access to healthcare to reduce racial disparities. Further investigation is required to evaluate whether these treatment patterns are similar within the general population. Disclosure: No